2004
DOI: 10.24310/abm.v29i0.7221
|View full text |Cite
|
Sign up to set email alerts
|

Etude de polyphénols des feuilles d’une endémique ibéro marocaine, Thymelaea lythroides.

Abstract: RÉSUMÉ: Etude de polyphénols des feuilles d’une endémique ibéro marocaine, Thymelaea lythroides. Thymelaea lythroides (Thyméléacées) est une endémique ibéro marocaine, largement répandue dans la région du Gharb (forêt de Mamora). Elle fait partie de la panoplie des plantes médicinales et aromatiques du Maroc. En raison du manque d’informations phytochimiques sur l’espèce, des études antérieures ont eu pour objet une recherche de l’activité antifongique de ses extraits et un screening phytochimique. Ce dernier … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(38 citation statements)
references
References 5 publications
2
35
0
1
Order By: Relevance
“…From analysis, we confirmed that the aqueous extract of T. Hirsuta collected in Morroco was also rich in flavonoids, alkaloids, sterols, caumaris and tannins, and there was no saponins and free quinonoids (Table 1) like described in other studies (Djeridane et al, 2005;Dohou et al, 2004;El-Beheiry et al, 2000;Garcia-Granadoset al, 1980).…”
Section: Chemical Constituentssupporting
confidence: 85%
“…From analysis, we confirmed that the aqueous extract of T. Hirsuta collected in Morroco was also rich in flavonoids, alkaloids, sterols, caumaris and tannins, and there was no saponins and free quinonoids (Table 1) like described in other studies (Djeridane et al, 2005;Dohou et al, 2004;El-Beheiry et al, 2000;Garcia-Granadoset al, 1980).…”
Section: Chemical Constituentssupporting
confidence: 85%
“…The qualitative phytochemistry of the dry extract was achieved by colorimetric reactions and precipitation by specific chemical reagents according to the protocols given in the literature [24][25][26]. These tests revealed the presence of a number of compound groups of the three extracts.…”
Section: Screening Phytochemical Analysismentioning
confidence: 99%
“…4c , d , e ). These features are recognized as the microscopic hallmark of contact dermatitis [ 28 ]. Interestingly, our study demonstrated that this DNFB-induced features of inflammation were also suppressed upon CS treatment, as shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The methanol extract was subjected to phytochemical analysis for constituent identification using the phytochemical methods, which were previously described [ 28 ]. In general, tests for the presence or absence of phytochemical compounds involved the addition of an appropriate chemical agent to the preparation in a test tube.…”
Section: Methodsmentioning
confidence: 99%